Populus trichocarpa encodes small, effector-like secreted proteins that are highly induced during mutualistic symbiosis - Jonathan M. Plett (Nature Portfolio, 2017)
Abstract During symbiosis, organisms use a range of metabolic and protein-based signals to communicate. Of these protein signals, one class is defined as ‘effectors’, i.e., small secreted proteins (SSPs) that cause phenotypical and physiological changes in another organism. To date, protein-based effectors have been described in aphids, nematodes, fungi and bacteria. Using RNA sequencing of Populus trichocarpa roots in mutualistic symbiosis with the ectomycorrhizal fungus Laccaria bicolor, we sought to determine if host plants also contain genes encoding effector-like proteins. We identified 417 plant-encoded putative SSPs that were significantly regulated during this interaction, including 161 SSPs specific to P. trichocarpa and 15 SSPs exhibiting expansion in Populus and closely related lineages. We demonstrate that a subset of these SSPs can enter L. bicolor hyphae, localize to the nucleus and affect hyphal growth and morphology. We conclude that plants encode proteins that appear to function as effector proteins that may regulate symbiotic associations.